The Effects Of Financial And Technological Literacies On Sustainability Performance Of Ikm In Indonesia: Mediating Role Of Competitive Advantage - Satiti, Novita Ratna (2024)
Businesses today face evolving challenges and opportunities, particularly in the fields of finance and technology. It is crucial to stay informed about these changes to maintain competitiveness. In the small and medium enterprises (sme) sector, a particular obstacle is evident: many owners/managers believe that strategic planning is only for large companies, leading to a lack of strategic direction. Financial literacy (fl) and technology literacy (tl) are essential for smes, as these skills directly impact their ability to gain competitive advantage (ca) and achieve sustainable performance (sp), in alignment with the sustainable development goals (sdgs). This study aims to investigate the relationship between fl and tl, and how they contribute to ca and sp. Utilizing the resource-based view (rbv) theory and the triple bottom line (tbl) theory, with ca as a mediator, this study proposes a comprehensive framework. Data was collected through a quantitative survey using a stratified random sampling technique involving 407 sme respondents and was analyzed using partial least squares structural equation modeling (pls-sem) and artificial neural networks (ann). Findings highlight fl, particularly internal and external aspects of companies, along with specific dimensions of tl (ict policies and human resources in ict), as critical factors influencing ca. Additionally, it was found that ca positively impacts sp, serving as a mediator between fl and sp. However, ca only mediates the relationship between ict policies and sp within tl, not for other tl dimensions. The study's conclusions were validated using ann.